THE INFLUENCE OF VILLAGE HEAD LEADERSHIP ON COMMUNITY PARTICIPATION IN DEVELOPMENT IN BAGAN CEMPEDAK VILLAGE, RANTAU KOPAR DISTRICT, ROKAN HILIR REGENCY - Awang Pratama; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
This research was conducted in Bagan Cempedak Village, Rantau Kopar District, Rokan Hilir Regency. The purpose of this study was to determine the effect of village head leadership on community participation in development in Bagan Cempedak Village. The population in this study were heads of families in Bagan Cempedak Village. The sample in this study was 81 heads of families with random sampling techniques, using the 10% slovin formula. This study used quantitative descriptive data analysis using the simple linear regression analysis method and the data was analyzed using the SPSS version 25 program. The results of this study indicate that Village Head Leadership has a positive and significant effect on Community Participation in Bagan Cempedak Village. From the results of the Determination test, the R Square value is 0.513 or 51.3%. This means that 51.3% of the variable (Community Participation) is influenced by the variable (Village Head Leadership). The remaining 48.7% is influenced by other variables not examined in this study.